The Relationship of ICH Score and 30-Day Mortality Rate in Hemorrhagic Stroke Patient: Systematic Review and Meta-Analysis - Samuel Sitohang; Sabri (Talenta Publisher, 2021)
Hemorrhagic stroke is a type of stroke that causes more deaths than ischemic stroke. The prognosis of hemorrhagic stroke patients can be determined with ICH Score. ICH score has a value range of 0-6. The variables of ICH Score are GCS score (0-2), bleeding volume (0-1), intraventricular bleeding (0-1), infratentorial origin (0-1), and age (0-1). Aim: This meta-analysis study aims to determine the relationship between ICH Score and 30-day mortality rate in hemorrhagic stroke patients. Methods: This meta-analysis study uses online literature sourced from Pubmed, Science Direct and Google Scholar. Result: Based on data analysis, there is a significant relationship between the ICH Score and the mortality rate in hemorrhagic stroke patients (OR 18.04, 95% CI: 10.65; 30.55). Analysis of the ICH Score accuracy found that the ICH Score had high accuracy to predict the mortality of hemorrhagic stroke patients (AUC 0.827, 95% CI: 0.796; 0.858). Conclusion: ICH Score has a significant relationship with the 30-day mortality rate in hemorrhagic stroke patients and has high accuracy for predicting mortality in hemorrhagic stroke patients.